MODERN CONCEPTION AS TO THE FUNCTIONAL MORPHOLOGY OF THE OLFACTORY SYSTEM AND ITS CHANGES UNDER THE INFLUENCE OF SOME EXOGENOUS POLLUTANTS - A.D. Shkodina; R.M. Hrinko; I.I. Starchenko (Проблеми екології та медицини)
The interaction between a body and an environment provides the main aspects of human life. The study of the functional structure of the olfactory analyzer plays an important role both in clinical and in experimental studies, but the question of its features in humans needs detailed research. The paper presents the modern data of the structural and functional organization of the olfactory analyzer. Particular attention is paid to the structural organization of olfactory bulbs as most complicated and least studied component of the olfactory analyzer. The morphological and functional changes of the olfactory analyzer are developing in some diseases and in action of adverse environmental factors are described while the accentuation is placed on the differences of the mechanism in the pathogenesis of damage to the olfactory analyzer, depending on the nature of the influence of pathogenic factors. In this way as the result of short-term intense effects of the pollutant, irreversible atrophic changes are primarily affected to the olfactory epithelium, thus, to some extent, preventing the spread of the toxin to other analyzer structures. Conversely, a long-term exposure to low doses usually retains the functional activity of the olfactory epithelium, while harmful substances penetrate the central unit of the olfactory analyzer. In such cases, the olfactory dysfunction can be diagnosed after a long time after the start of the cohort with certain pollutants. Currently, studies of the influence of exogenous toxins on various parts of the olfactory analyzer on animal experimental models are quite active. At the same time, the issue of functional and morphological changes in various structural components of the human olfactory analyzer under the influence of negative environmental factors remains poorly understood and requires further morphological and biochemical studies, in order to be able to further develop effective therapeutic and prophylactic means.